2008
DOI: 10.1071/ar08032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Australian Brassica napus genotypes for resistance to the downy mildew pathogen, Hyaloperonospora parasitica

Abstract: Downy mildew, caused by the pathogen Hyaloperonospora parasitica, is a severe disease of oilseed rape (Brassica napus) seedlings in some regions of Australia. Sixty-three cultivars of Australian spring-type oilseed rape were evaluated for their levels of resistance to five isolates of the downy mildew pathogen, using a cotyledon infection test under controlled-environment conditions. A high level of resistance, characterised by the absence of disease symptoms or only the appearance of very sparse sporulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Downy mildew, caused by Hyaloperonospora brassicae (formerly Peronospora brassicae or Hyaloperonosporaparasitica), infects rapeseed-mustard in Canada, several Asian and European countries, including the UK and France, and also China and India (Saharan, 1993) and Australia (Ge et al, 2008). Downy mildew is an important disease in India, where the predominant oilseed brassica grown is B. juncea, and where it can cause serious economic loss even during the seedling stage (Thakur and Mathur, 2002 (Meena et al, 2014).…”
Section: Downy Mildewmentioning
confidence: 99%
“…Downy mildew, caused by Hyaloperonospora brassicae (formerly Peronospora brassicae or Hyaloperonosporaparasitica), infects rapeseed-mustard in Canada, several Asian and European countries, including the UK and France, and also China and India (Saharan, 1993) and Australia (Ge et al, 2008). Downy mildew is an important disease in India, where the predominant oilseed brassica grown is B. juncea, and where it can cause serious economic loss even during the seedling stage (Thakur and Mathur, 2002 (Meena et al, 2014).…”
Section: Downy Mildewmentioning
confidence: 99%
“…However, in some instances, there was association of resistance at cotyledon stage with that expressed at the adult stage (Jensen et al, 1999a ; Wang et al, 2000 ). Similarly, screening tests on seedling cotyledons across B. napus cultivars were claimed to provide an accurate estimation of expression of field susceptibilities/resistance on seedling and more mature leaves for Downy Mildew (Ge et al, 2008 ). These contrasting findings indicate that the resistance outcome in the host against Downy Mildew is likely to be QTL-specific where the QTL is associated with developmental stages of the plant.…”
Section: Sources Of R Genes For Key Pathogensmentioning
confidence: 99%
“…Several major qualitative resistance loci to downy mildew have been identified in B. rapa and B. oleracea (Farinhó et al, 2007, Carlier et al, 2012. In addition, multiple sources of resistance have been reported in B. napus (Nashaat et al, 1997, Ge et al, 2008. They showed that the resistance is more likely to be controlled by a major resistance gene.…”
Section: Genetics Of Disease Resistance In Brassicamentioning
confidence: 99%
“…While it causes severe destruction on young seedlings, the disease still causes yield and quality reduction at adult-plant stages. For instance, in Australia, outbreaks of downy mildew disease at the early seedling stage have caused losses of canola production (Ge et al, 2008). Several major qualitative resistance loci to downy mildew have been identified in B. rapa and B. oleracea (Farinhó et al, 2007, Carlier et al, 2012.…”
Section: Genetics Of Disease Resistance In Brassicamentioning
confidence: 99%
See 1 more Smart Citation